Analisis Penunjang Keputusan Penerapan Quality of Work Life dalam Meningkatkan Motivasi Karyawan - Sukmawati, Anggraini; Cyrilla, Lucia; Andriana, Susan (Jurnal Manajemen, 2009)
Ever since the concept of Quality of Work Life (QWL) was first used over 30 years ago, arrange of definition and theoretical constructs have succeeded each other with the aim of mitigating the many problems facing the concePTÂ This study was aimed to improve employees motivation by implementing QWL programs in the cattle fattening industry as a case study.Â The research showed that according to Analytical Hierarchy Process (AHP), priority of main factors are: (1) participative job design; (2) democratic supervision; (3) participation on profit sharing; (4) quality circle; (5) participation in decision making process. Results of this analysis indicated that the formal program was suggested as a strategic alternative in implementing QWL. This finding contributes to operationalization of the QWL theory. Drawing on the dependent nature of employees and organizations, the implication are that the organization must provide support structures, such as employee development and career advancement opportunities, when seeking to transform the QWL. In this way, it can improve working conditions, achieve higher motivation from individual employees, and thus improve the performance of the organization.Keywords: Proses Hierarki Analitik, Job Design, Motivasi, Partisipasi, Quality of Work Life, Quality Circle.